Transcriptional profiling clarifies a program of enzalutamide extreme non-response in lethal prostate cancer - Anbarasu Kumaraswamy; Ya-Mei Hu; Joel A. Yates; Chao Zhang; Eva Rodansky; Dhruv Khokhani; Diana Flores; Zhi Duan; Yi Zhang; Shaadi Tabatabaei; Rachel Slottke; Shangyuan Ye; et al. (npj Precision Oncology)
Abstract The androgen receptor inhibitor enzalutamide is one of the principal treatments for metastatic prostate cancer. Most patients respond. However, a subset is primary refractory. Seeking to understand enzalutamide extreme non-response (ENR), we analyzed RNA-sequencing in biopsies from men treated prospectively on an enzalutamide clinical trial. We focused on those with ENR (progression within 3 months) vs. long-term response (progression after 24 months). We identified an ENR program linked to proliferation, epithelial-to-mesenchymal transition, and stemness. High expression of this program in additional datasets was independently linked to poor tumor control with AR targeting but favorable tumor control with docetaxel, another standard treatment. CDK2 was implicated in the ENR program. CDK2 suppression reduced the ENR program and viability of ENR program-high prostate cancer models. The ENR gene program is predictive of non-response to AR targeting. Patients whose tumors harbor this program may be good candidates for docetaxel or CDK2 inhibitor clinical trials.